Յոդի անբավարարությամբ չպայմանավորված վահանաձև գեղձի հիվանդությունների ռիսկի գործոնները Երևան քաղաքի բնակիչների շրջանում - Խռոյան, Ա․ Գ․; Աղաջանովա, Ե․ Մ․; Բաղդասարյան, Ս․ Է․; Դալլաքյան, Գ․ Գ․; Թադևոսյան, Ա․ Է․ (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Проведено исследование по типу случай-контроль, изучены некоторые факторы риска развития патологий щитовидной железы (ЩЖ), непосредственно не связанные с дефицитом йода. Показано, что недостаточное потребление морских продуктов, а также овощей, мяса, субпродуктов, орехов, богатых микроэлементами и витаминами, способствует повышению риска развития заболеваний ЩЖ. Особенно большое значение имеют такие продукты, как чеснок, томаты, оливковое масло. Определенное неблагоприятное значение имеет употребление алкоголя. Выявлена ассоциация заболеваний ЩЖ с семейной средиземноморской лихорадкой. A case-control study was conducted, some risk factors for the development of thyroid diseases not directly related to iodine deficiency were studied. It has been shown that insufficient consumption of seafood, as well as vegetables, meat, offal, nuts, rich in trace elements and vitamins, contribute to an increase in the risk of developing thyroid diseases. Products such as garlic, tomatoes, and olive oil are especially important. Alcohol consumption has a certain unfavorable effect. An association of thyroid diseases with familial Mediterranean fever was revealed.
Keywords: Endocrinology